1986
DOI: 10.4319/lo.1986.31.5.1039
|View full text |Cite
|
Sign up to set email alerts
|

Competition in zooplankton communities: Suppression of small species by Daphnia pulex1

Abstract: The hypothesis that a large zooplankton herbivore, Daphnia pulex, can competitively reduce the abundance of resident zooplankton when colonizing a community of small species was tested in two lakes. When introduced to enclosures in eutrophic Larimore Pond, D. pulex decreased phytoplankton abundance by an order of magnitude, resulting in drastically reduced densities of Tropocyclops prasinus and Mesocyclops edax, the two dominant crustaceans in the pond. Daphnia pulex was also added to enclosures in oligo-mesot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 31 publications
6
102
1
1
Order By: Relevance
“…Also, many studies have demonstrated the competitive dominance of daphnids over smaller herbivores such as Keratella cochlearis (Neill 1984;Gilbert and Stemberger 1985;Arvola and Salonen 2001), Kellicottia sp. (Neill 1984) and copepod nauplii (Vanni 1986), which is consistent with our results.…”
Section: Demonstrated That Prédation Bysupporting
confidence: 82%
“…Also, many studies have demonstrated the competitive dominance of daphnids over smaller herbivores such as Keratella cochlearis (Neill 1984;Gilbert and Stemberger 1985;Arvola and Salonen 2001), Kellicottia sp. (Neill 1984) and copepod nauplii (Vanni 1986), which is consistent with our results.…”
Section: Demonstrated That Prédation Bysupporting
confidence: 82%
“…Neil1 (1984Neil1 ( , 1985 showed that removal of Daphnia rosea from Gwendoline Lake enclosures caused marked increases in the fertilities and population densities of planktonic rotifers, mostly K. cochlearis and Kellicottia longispina. Vanni (1986) found that adding D. pulex did not significantly reduce populations of K. cochlearis and P. vulgaris in Larimore Pond and Dynamite Lake enclosures but did significantly suppress the Trichocerca multicrinis population in the latter enclosures. The absence of a significant Daphnia effect on most of his rotifer populations may be explained, however, by low and declining rotifer densities in both control and expcrimental enclosures at both sites, by quite low Daphnia densities in the experimental enclosures in Dynamite Lake, and by limi ted replication.…”
Section: Resultsmentioning
confidence: 90%
“…Lampert et al, 1986;Vanni, 1986). In the enclosure experiment, mean cladoceran biomass was never greater than 25jig T '.…”
Section: Discussionmentioning
confidence: 95%